Direct current electrical performances of cable accessory insulation EPDM modified by grafting polar-group compound - Li, Zhong-Yuan (2023)
In order to improve electrical matching between ethylene-propylene-diene misch-polymere (EPDM) reinforce insulation and crosslinked polyethylene (XLPE) main insulation in direct current (DC) cable accessories, the glyceryl monooleate (GMO) organic compound composed of several polar-groups and one long carbon chain is employed for chemical graft modification on EPDM to ameliorate DC electrical performances. Charge trap characteristics are analyzed by testing thermal stimulation current (TSC) and verified by calculating first-principles electronic properties to elucidate the GMO-graft-modified charge trapping mechanism accounting for DC electric conductance and dielectric breakdown. The grafted GMO molecules introduce substantial shallow charge traps that lead to nonlinear profiles of electric conduction versus electric field and cause hopping transports of percolation conductance. Electric conductance of EPDM is significantly improved by GMO graft for electrical matching with XLPE, while a high level of dielectric breakdown strength is retained sufficiently for reinforce insulation in cable accessories. Shallow charge traps introduced by GMO graft are capable of capturing charge carriers to form homocharge layers near electrodes which can scatter the transporting charge carriers and exclude further charge injections, thus to mitigate the dielectric breakdown strength reduction caused by electric conductivity improvement. Electric field finite-element simulations demonstrate that the electric field in DC cable terminals can be evidently homogenized by using GMO-grafted EPDM as reinforce insulation.